Spy [videorecording (DVD)] - Feig, Paul; McCarthy, Melissa, 1969-; Statham, Jason, 1967-; Byrne, Rose; Law, Jude, 1972- (Twentieth Century Fox Home Entertainment, 2015)
Susan Cooper is an unassuming, deskbound CIA analyst, and the unsung hero behind the Agency's most dangerous missions. But when her partner falls off the grid and another top agent is compromised, she volunteers to go deep undercover to infiltrate the world of a deadly arms dealer, and prevent a global crisis.